The expected roles of school and family in the learning of general education diploma students in the Sultanate of Oman considering the Covid-19 pandemic from the students’ point of view - Almatari, Ali Said Sulaiyam; Alharmali, Amal Abdullah (Journal of Educational and Psychological Sciences, 2021)
The study aimed to uncover the expected school and family roles in the learning of general education diploma students in the Sultanate of Oman considering the Covid-19 pandemic from the students’ point of view. The study adopted the descriptive, analytical, and qualitative approach, and the study sample reached (220) male and female students for the academic year 2020-2021 AD, and the study tool consisted of a questionnaire divided into two parts. The general diploma in the distance, in addition to the researchers’ use of the interview method to find out the challenges that students face in distance learning, and the results of the study showed: that the expected level of the school’s roles in learning for general education diploma students from a distance in the Sultanate of Oman in light of the Covid-19 pandemic from the point of view The students themselves were to a large degree and with an average of (4.59), and the roles of the family in the learning of students of general education diploma remotely in the Sultanate of Oman in light of the Covid-19 pandemic from the viewpoint of the students themselves was to a large degree and with an average of (4.48). The results also showed that there are no statistically significant differences in the total score in the general diploma students ’perceptions of the expected roles of the family and the school according to the variable of gender and educational governorate and that among the most important challenges facing the success of the distance education experience in light of the Corona pandemic from the students’ point of view are: Internet (its services - availability - its cost), and hardware (availability - its cost), and the results revealed ways to overcome previous challenges, including strengthening the link between school and home to achieve cooperation in activating distance education, providing devices (laptop computer - Smart device) for students at nominal prices with support for their purchase. Improving the infrastructure and its technical and technological equipment in public schools.